ENGINEERING FORMULATION AND MATHEMATICAL FORMULATION OF THE PROBLEM OF ENERGY EQUIVALENCE OF WATER SUPPLY SYSTEMS - Kadirov, M.Y (Educational Research in Universal Sciences, 2022)
One of the main circulations of today’s water supply system is the emergence of various circulations in the long-term maintenance of the network, the system allows for shortcomings in the calculation of the volume and the rapid growth of the population, and as a result of this, the pipes lead to rapid failure. Given the fact that the master’s thesis comes from these circulations and the rapid wear of the pipes, it is aimed at calculating the system and solving the problems in the design of this system with the most optimal one. Due to these circulations in the water supply, the ways of solving the problems in the system using different methods, the distribution of the flow in the water supply system with the help of modern programs were clearly summarized.